Patterns in conceptual metaphors, image metaphors, and similes in Hosea - Pohlig, J. N. (Journal for semitics, 2006)
This paper seeks to contribute to an understanding of the world view of Hosea and his audiences, by asking whether this prophet expected his hearers to understand various figures of speech easily or with difficulty. First, conceptual metaphors are posited as normally comprising language that is considered fairly literal by native speakers. Secondly, similes are presented as conceptual associations that are regarded as less literal and more difficult. Three kinds of conceptual manipulations in Hosea are tabulated: humanization (the attribution of human properties to God, animals or objects), animalization (the attribution of animal properties to non-animal entities), and objectification (the attribution of object properties to non-object entities). The paper concludes that in the book of Hosea as we have it, YHWH, animals, and objects were very readily conceptualized in human terms; but that conceptualization of YHWH and humans in terms of animals or objects was seen as more difficult. Abstractions were easily conceptualized as objects, but entities conceptualized as like entities were considered to be more difficult.